Scientists warning on the ecological effects of radioactive leaks on ecosystems - Bonacic, Cristian; Medellin, Rodrigo A.; Ripple, William; Sukumar, Raman; Ganswindt, Andre; Padua, Suzana M.; Padua, Claudio; Pearl, Mary C.; Aguirre, Luis F.; Valdés, Lourdes Mugica; Buchori, Damayanti; Innes, John L.; et al. (Frontiers in Ecology and Evolution, 2023)
A nuclear leakage or tactical nuclear weapon in a limited war could cause immense and long-lasting ecological consequences beyond the direct site of exposure. We call on all scientists to communicate the importance of the environmental impact of such an event to all life forms on Earth, including humankind. Changes to ecosystem structure and functioning and species extinctions would affect the biosphere for an unknown time frame. Radiation could trigger cascade effects in marine, atmospheric and terrestrial ecosystems of a magnitude far beyond human capabilities to mitigate or adapt. Even a "tactical nuclear war" could alter planet Earth's living boundaries, ending the Anthropocene era.